IS THE GROWTH WITHOUT THE “NEW NORMALITY” POSSIBLE? STRATEGIC INITIATIVES OF EMERGING ECONOMIES - M. A. Eskindarov; V. V. Perskaya (Финансы: теория и практика, 2017)
The paper analyzes the epistemology of the term “new normality” and proves that its use meets largely the interests of developed economies. The provided data demonstrate that for “the American idea of self-identification” in the international community this approach is utterly unacceptable and it rather concerns national economies which are not incorporated into the “satellite mainstream” of the implementation of the US economic interests. It is emphasized that the SCO, BRICS and EAEU members state are developing economies with a sufficient internal resource potential, including the human capital. They are setting up a system of their own national interests that is implemented in the current world, among other things, based on increasing the interaction and cooperation of efforts. The restructuring of national economies towards creation of new jobs, improvement of the living standards, development of the real sector and reducing dependence on developed economies, particularly the foreign capital dependence, is regarded as a decline in the level of development. But in fact, this process means the gradual disintegration of the monopolar configuration of the world economy with the dominance of the US economy and the US national interests.